2004
DOI: 10.1196/annals.1331.058
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cell Proliferation and Gene Expression by α‐Tocopheryl Phosphates: Relevance to Atherosclerosis and Inflammation

Abstract: The effect of a mixture of alpha-tocopheryl phosphate plus di-alpha-tocopheryl phosphate (TPm) was studied in vitro on two cell lines, RASMC (from rat aortic smooth muscle) and human THP-1 monocytic leukemia cells. Inhibition of cell proliferation by TPm was shown in both lines and occurred with TPm at concentrations lower than those at which alpha-tocopherol was equally inhibitory. TPm led in nonstimulated THP-1 cells to inhibition of CD36 mRNA and protein expression, to inhibition of oxidized low-density lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 6 publications
0
18
1
Order By: Relevance
“…α-TOC is known to inhibit PKC activity in a wide variety of cells [32][33][34] including neutrophils [5,6,35]. In human neutrophils, the activation and translocation of PKC from its inactive form found in the cytosol to the cell membrane are key events in phorbol-ester-induced signaling and are required to induce O 2 •− production [36].…”
Section: Discussionmentioning
confidence: 99%
“…α-TOC is known to inhibit PKC activity in a wide variety of cells [32][33][34] including neutrophils [5,6,35]. In human neutrophils, the activation and translocation of PKC from its inactive form found in the cytosol to the cell membrane are key events in phorbol-ester-induced signaling and are required to induce O 2 •− production [36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that the antioxidant activities of TocP are not mainly involved in the repressive effects on tumor invasion, and the anti-invasive effect of TocP seems to be due to the effect of the parent compound Toc. It has been also shown that TocP is highly resistant to hydrolysis by both chemical and enzymatic actions, which indicates that its effect is not related to the hydrolytic conversion to free tocopherol (4,7,9,10,43). Furthermore, it was shown that TocP has a more marked potency than the non-esterified molecule in several studies (4,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 98%
“…It has been also shown that TocP is highly resistant to hydrolysis by both chemical and enzymatic actions, which indicates that its effect is not related to the hydrolytic conversion to free tocopherol (4,7,9,10,43). Furthermore, it was shown that TocP has a more marked potency than the non-esterified molecule in several studies (4,(8)(9)(10). In addition, a previous study indicates that TocP forms a barrier that might inhibit the transfer of radicals from one polyunsaturated fatty acid to another, so that TocP has a potent antioxidant effect of its own, but not due to the conversion into Toc (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation has the potential to favorably modify the properties and actions of lipophilic drugs, which may otherwise manifest toxicity owing to their inherent high lipophilicity [68,69]. Troglitazone was designed with a 2, 4-thiazolidinedione nucleus to which a highly hydrophobic a-tocopherol moiety is added to confer anti oxidant properties [70].…”
Section: Role Of Proteoglycans In the Response-to-retention Hypothesismentioning
confidence: 99%